Survival of European plaice discarded from coastal otter trawl fisheries in the English Channel. (15th December 2017) - Morfin, Marie; Kopp, Dorothée; Benoît, Hugues P.; Méhault, Sonia; Randall, Peter; Foster, Robert; Catchpole, Thomas
Abstract: Species that have a high likelihood of surviving the discarding process have become great concern since the European Union reformed the Common Fisheries Policy and enacted a landing obligation prohibiting the discarding any individuals of species under quota. Among species presenting an elevated survival potential, plaice ( Pleuronectes platessa ) is one of the most discarded in the coastal otter trawl fishery in the English Channel. The objective of this study is to provide the most reliable estimates of plaice survival after release in commercial conditions, and to identify the factors that influence survival rates. A captivity experiment was conducted in January–February in the English fishery to assess the survival of discarded plaice as a function of a semi-quantitative index of fish vitality, which has been demonstrated to be a good proxy of fish survival in comparable fishing and environmental conditions. This study examined the potential of this index to estimate discard survival in three trials from the English and French fisheries and at three different seasons. The vitality index was then used to analyse the influence of several factors (fishing practices, environmental conditions and fish biological characteristics) on the discard survival. The survival rates for plaice were accurately estimated at 62.8% in January–February, 66.6% in November and 45.2% in July. While these rates remained substantial whatever the fishing, environmental or fish biological conditions, the time fish spent on the deck, the bottom and air temperatures, the tow depth and the fish length had a significant influence on plaice survival. In practice, plaice survival could be enhanced by releasing the fish early during catch sorting and avoiding exposure to extreme air temperatures. Highlights: Survival rates of European plaice in the English Channel otter trawl fishery. Between 45 and 67% of plaice survived depending on seasons and vessel. Semi-quantitative vitality index is a relevant proxy of plaice discard survival. Handling duration, temperature and fish length were the main survival drivers. Release back to the sea during catch sorting substantially increases survival.